Governance of web-based idea management system rewards: From the perspective of open innovation - Elina Mikelsone; Jean-Pierre Segers; Aivars Spilbergs (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Digitisation of business processes has attracted practitioner attention across a wide range of industries as it enables enterprises to better manage their processes and improve results. The rate of digitisation has grown over the last decade and has become essential for enterprises to handle unforeseen disruptions and promote better management of resources. The COVID-19 pandemic is one example of a recent major disruption that caught enterprises off-guard and had a major impact on their value chains. The adoption of digitisation of business processes has significantly sped up to improve enterprise and their value chain resilience and enable enterprises to survive and potentially thrive in today's uncertain environment. Through this movement, innovative companies have embraced idea management to develop new business models and achieve competitive advantage. One of the major digital tools that support enterprises in their idea management efforts is web-based idea management systems. This study aims to show how enterprises can manage the rewards of platforms, such as web-based idea management systems, to achieve a first-in-class quality and quantity of ideas sourced from the stakeholders involved in these platform-based ecosystems. To reach this aim, a global survey study was conducted involving over 400 responses from enterprises that use web-based idea management systems and consequent results were analysed. The impact of intrinsic and extrinsic rewards on the results of enterprises is a well-researched area. To further verify the results, the authors have conducted ten expert interviews and a qualitative analysis of a data set sourced from a database that contained 129 company entries that utilise web-based idea management systems and was available for this research that was conducted over a two-year period. Results strongly indicate that mixed and financial reward type tasks result in a higher quantity of ideas created, however, higher idea quality-i.e., ideas selected-is higher for financial reward tasks. The research highlights that there could be differences between different web-based idea management systems application groups.
Keywords: 650; idea management; idea management systems; ideation; innovation; innovation management; open innovation; rewards